Association between activity limitations and pain in patients scheduled for total knee arthroplasty. Issue 1 (December 2016) - Usiskin, Ilana; Yang, Heidi; Deshpande, Bhushan; Collins, Jamie; Michl, Griffin; Smith, Savannah; Klara, Kristina; Selzer, Faith; Katz, Jeffrey; Losina, Elena
Abstract Background Historically, persons scheduled for total knee arthroplasty (TKA) have reported severe pain with low demand activities such as walking, but recent data suggests that TKA recipients may have less preoperative pain. Little is known about people who elect TKA with low levels of preoperative pain. To better understand current TKA utilization, we evaluated the association between preoperative pain and difficulty performing high demand activities, such as kneeling and squatting, among TKA recipients. Methods We used baseline data from a randomized control trial designed to improve physical activity following TKA. Prior to TKA, participants were categorized according to Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain scores: Low (0–25), Medium (26–40), and High (41–100). Within each group, limitations in both low demand and high demand activities were assessed. Results The sample consisted of 202 persons with a mean age of 65 (SD 8) years; 21 %, 34 %,  and 45 % were categorized in the Low, Medium, and High Pain groups, respectively. Of the Low Pain group, 60 % reported at least one of the following functional limitations: limited flexion, limp, limited walking distance, and limitations in work or housework. While only 12 % of the Low Pain group reported at least moderate pain with walking on a flat surface, nearly all endorsed at least moderate difficulty with squatting and kneeling. Conclusions A substantial number of persons scheduled for TKA report Low WOMAC Pain (≤25) prior to surgery. Persons with Low WOMAC Pain scheduled for TKA frequently report substantial difficulty with high demand activities such as kneeling and squatting. Studies of TKA appropriateness and effectiveness for patients with low WOMAC Pain should include measures of these activities. Trial registration IdentifierNCT01970631 ; Registered 23 October 2013.